2013
DOI: 10.1002/cncr.28300
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of caldesmon is associated with lymph node metastasis and poorer prognosis in patients with oral cavity squamous cell carcinoma

Abstract: BACKGROUND A previous comparative tissue proteomics study by the authors of the current study led to the identification of caldesmon (CaD) as one of the proteins associated with cervical metastasis of oral cavity squamous cell carcinoma (OSCC). In the current investigation, the authors focused on the potential functions of CaD in patients with OSCC. METHODS CaD expression was examined in tissue samples from 155 patients using immunohistochemical analysis. The expression of CaD variants was determined by Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Images of stained slides were obtained using a ScanScope CT automated slide-scanning system (Aperio Technologies, Vista, CA). The expression level of HMGA2 or MIF was scored using a combined scoring method that accounted for both the staining intensity and the percentage of stained cells, as previously described 14 20 52 53 54 . Strong, moderate, weak, and negative staining intensities were scored as 3, 2, 1, and 0, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Images of stained slides were obtained using a ScanScope CT automated slide-scanning system (Aperio Technologies, Vista, CA). The expression level of HMGA2 or MIF was scored using a combined scoring method that accounted for both the staining intensity and the percentage of stained cells, as previously described 14 20 52 53 54 . Strong, moderate, weak, and negative staining intensities were scored as 3, 2, 1, and 0, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…CAD is a major actomyosin binding protein that is critically implicated in the regulation of the microfilament network, and acts as an important modulator of various cell functions. CAD expression and its role in several solid cancers have been reported in recent studies [ 11 15 ]. However, the results are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…CALD1 participates in the interaction of actin and myosin and its expression and function in MFs has been studied (Lazard et al., ; Kalekou et al., ; Hai and Gu, ; Council and Hameed, ; Huang et al., ; Leung et al., ; Salgueiredo‐Giudice et al., ). Elevated expression of this protein was also observed in oral SCCs (Méndez et al., ) and its overexpression was associated with lymph node metastasis and poor prognosis in patients with oral cavity SCC (Chang et al., ). Additionally, it was shown that CALD1 phosphorylation reduced its binding to actin and myosin thus promoting pro‐migratory and pro‐invasive activities in breast cancer cells (Schwappacher et al., ).…”
Section: Discussionmentioning
confidence: 96%